RETRACTED: Inheritance of morpho economic traits in f1-f2 descendants of cotton - Norov Bekzod; Amanturdiyev Alisher; Kuchkorov Orip; Raimberdiev Kholygit; Mirakhmedov Mirvakhob; Khamrokulov Isfandiyar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001